Astaxanthin accumulation in Microcystis aeruginosa under different light quality. (February 2022) - Zhou, Xiaonan; Zheng, Tiefeng; Xie, Yike; Zou, Shuzhen; Xu, Sun; Lai, Meng; Zuo, Zhaojiang
Highlights: Purple light promoted M. aeruginosa cell growth among the 4 light quality treatments. Purple light raised the photosynthetic rate by up-regulating related gene expression. Purple light increased astaxanthin content by raising expression of related genes. M. aeruginosa has the potential for astaxanthin production under purple light. Abstract: The aim of this work was to uncover the astaxanthin biosynthesis mechanism in Microcystis aeruginosa under optimum light quality, and promote astaxanthin production using this alga. Among purple, blue and red light, only purple light promoted M. aeruginosa cell growth compared with white light, due to up-regulating expression of the genes related with DNA replication. An increase was detected in the photosynthetic rate under purple light, which should be caused by the raised carotenoid content and up-regulation of the genes associated with light reaction and carbon fixation. Compared with white light, purple light increased the levels of β-carotene, zeaxanthin and astaxanthin by up-regulating expression of the genes related with methylerythritol-4-phosphate pathway (MEP) and astaxanthin biosynthesis. For red and blue light, they did not impact or declined the content of astaxanthin and its precursors. Therefore, purple light promoted M. aeruginosa cell growth and astaxanthin production by up-regulating related gene expression.